2017
DOI: 10.1016/j.jvscit.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment with flow-diverting stents of symptomatic superior mesenteric artery after dissection aneurysm

Abstract: Isolated and spontaneous superior mesenteric artery dissection is a rare cause of acute abdominal pain. Whereas there is widespread consensus on conservative treatment of asymptomatic forms, revascularization would seem indicated in symptomatic complicated cases. A 73-year-old man presented with worsening epigastric pain. A computed tomography scan revealed an isolated and spontaneous superior mesenteric artery dissection with aneurysmal evolution of the false lumen, involving multiple side branches. The postd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…[21][22][23][24] Further, many studies have reported the use of stents for patients with AMI caused by SIDSMA. 5,[25][26][27] This approach may be effective for preventing the progression of bowel necrosis. However, it remains controversial because of some reported failures.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] Further, many studies have reported the use of stents for patients with AMI caused by SIDSMA. 5,[25][26][27] This approach may be effective for preventing the progression of bowel necrosis. However, it remains controversial because of some reported failures.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical management remains a mainstay of treatment for failed conservative management, vascular compromise or an acute abdomen. Endovascular treatments should be considered with use of a flow diverting stent in patients with suspected intestinal ischemia, angina abdominis, worsening abdominal pain despite conservative management, true lumen compression >80%, SMA aneurysm of >2 cm or dissection progression [ 1 , 2 , 4 , 8 ]. For patients presenting with evidence of advanced intestinal ischemia or aneurysmal rupture, emergent open surgical intervention is indicated such as SMA re-implantation, resection or repair of the affected segment with interposition bypass or graft [ 1 , 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated spontaneous superior mesenteric artery (SMA) dissection is a rarely reported and potentially fatal cause of acute abdominal pain. In a MEDLINE literature search in 2011 only 168 cases were reported with an estimated incidence of 0.06% in post-mortem studies [ 1 , 2 ]. Clinical presentation of SMA spontaneous dissection has been found to most commonly occur in males in their mid-50s presenting with acute epigastric pain usually after overeating and drinking [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations